Swamp Angel - Isaacs, Anne. (Dutton Children's Books, 1994)
Along with other amazing feats, Angelica Longrider, also known as Swamp Angel, wrestles a huge bear, known as Thundering Tarnation, to save the winter supplies of the settlers in Tennessee.